A techno-economic assessment of bioethanol production from switchgrass through biomass gasification and syngas fermentation. (1st July 2023) - Regis, Francesco; Monteverde, Alessandro Hugo Antonio; Fino, Debora
Abstract: The consumption of fossil fuels, which are not economically and environmentally sustainable, can be reduced by producing biofuels, such as bioethanol. This study presents a reproducible model of the ethanol production process developed with Aspen Plus® software. The work's goal is to enhance the amount of ethanol produced per tonne of biomass and, therefore, the carbon yield of the process. The main steps of the process are the gasification of the pretreated switchgrass, the cleaning of the syngas obtained, the fermentation of the syngas to ethanol and its purification. The parameters relating to gasification were set to produce syngas with an optimal composition for the fermenter. A discounted cash flow analysis was used to determine the minimum ethanol selling price for different plant scales and H2 prices. By enriching the syngas with green H2 and adopting an optimal bioreactor, a remarkable ethanol yield of 1015.04 L/t of switchgrass can be obtained. Considering a plant size of 750, 000 t/y of switchgrass, the minimum ethanol selling price is 1.07 $/L for the base scenario and is further lowered to 0.77 $/L for the 2050 H2 scenario. The potential savings of building more plants were also assessed thanks to the learning effects. Graphical abstract: Image 1 Highlights: Gasification set to produce an optimal syngas composition for the fermenter. Considerable ethanol yield of 1015.04 L/t switchgrass. Adding green hydrogen to the syngas increase the process carbon yield of 23%. Minimum ethanol selling price of 1.07 $/L processing 750000 t/y of switchgrass. Reduction of almost 30% of the ethanol price considering 2050 green H2 scenario.